Kidney transplantation from a living donor with renal artery fibromuscular dysplasia: A case report on arterial grafting of the donor renal artery - Matsushita, Yuto (IJU Case Rep, 2020)
INTRODUCTION: Renal artery fibromuscular dysplasia is generally considered a contraindication of kidney transplantation, since fibromuscular dysplasia occasionally induces hypertension or renal insufficiency in the recipient and/or donor. To date, limited information remains available with respect to whether kidneys with renal arterial fibromuscular dysplasia can be successfully transplanted. CASE PRESENTATION: A 53‐year‐old potential donor was diagnosed with fibromuscular dysplasia of the right renal artery. Laparoscopic right nephrectomy was performed, and the affected portion was resected and reconstructed using the harvested internal iliac artery. Transplantation was successful and the serum creatinine level was <2 mg/dL for 3 years after surgery. CONCLUSION: If reconstruction of the diseased artery could be safely performed, transplantation using a kidney from a donor with renal artery fibromuscular dysplasia may be considered.